2015
DOI: 10.2983/035.034.0341
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Mediterranean Bivalve Mollusc Aquaculture to Climate Change, Ocean Acidification, and Other Environmental Pressures: Findings from a Producer Survey

Abstract: Human-induced climate change and ocean acidification are global environmental phenomena with a common driver: anthropogenic emissions of carbon dioxide. Both processes potentially threaten the Mediterranean bivalve mollusc aquaculture sector, which is economically relevant to several regions and countries. Detrimental effects on bivalve mollusc species might arise from the associated increase in sea surface temperature, pH reduction, higher frequency of extreme climatic events, and possible synergies with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…This signal is stronger in the shallowest portion (0-20 m) of the water column, but along the eastern coasts of the Levantine Basin this effect is still evident down to about 40 m depth. Figure 4 shows the change in number of sites at all considered depths, for either C. rubrum presence records (Harmelin, 2006) or mussel culture facilities (location points from Rodrigues et al, 2015), where at least one of the considered MHWs occurred. As our focus is on low motility (benthic) species, our maps are relevant just for a narrow strip along the coastline, however we choose to retain also the open sea for readers that might be interested in the epipelagic environment.…”
Section: Change In Temperature Regimes In the Mediterranean Seamentioning
confidence: 99%
See 1 more Smart Citation
“…This signal is stronger in the shallowest portion (0-20 m) of the water column, but along the eastern coasts of the Levantine Basin this effect is still evident down to about 40 m depth. Figure 4 shows the change in number of sites at all considered depths, for either C. rubrum presence records (Harmelin, 2006) or mussel culture facilities (location points from Rodrigues et al, 2015), where at least one of the considered MHWs occurred. As our focus is on low motility (benthic) species, our maps are relevant just for a narrow strip along the coastline, however we choose to retain also the open sea for readers that might be interested in the epipelagic environment.…”
Section: Change In Temperature Regimes In the Mediterranean Seamentioning
confidence: 99%
“…A questionnaire-based study of Mediterranean mollusc producers (Rodrigues et al, 2015) from 12 coastal regions and 6 countries highlighted how episodes of partial or total mortality related to high water temperature are currently widespread; other studies (Anestis et al, 2007(Anestis et al, , 2010Gazeau et al, 2014) identified the threshold of 25 • C as critical for mussels physiological activities, indicating that Mediterranean mussels may already live close to their physiological limits.…”
Section: Introductionmentioning
confidence: 99%
“…Various causes have been identified for MMB outbreaks, including: high sea temperatures and heat waves (Cheney et al 2000, Ortega et al 2012, Rodrigues et al 2015; changes in salinity (Xiao et al 2005), turbidity, and pH; high primary production (Cheney et al 2000, Mydlarz et al 2006; eutrophic waters (Friedman and Hedrick 1991); invasive species as competitors or predators (Matsuyama 1999, McKindsey et al 2007; pathogens (Elston et al 1987); and density-dependent factors (Brazeiro andDefeo 1999, Xiao et al 2005).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although temperature will not be the only change to impact bivalves, it has been shown to be the most deterministic factor influencing shellfish growth and distribution, and is one of the most widely studied abiotic factors related to climate change (Zippay and Helmuth, 2012;Rodrigues et al, 2015;Buckley and Huey, 2016;Filgueira et al, 2016). Warming oceans are modifying current natural ranges of many marine species (e.g., Diederich et al, 2005;Jones et al, 2009Jones et al, , 2010Rinde et al, 2016;Shelmerdine et al, 2017).…”
Section: Introductionmentioning
confidence: 99%